Relative Children’s Lipid Accumulation Product Is a Novel Indicator for Metabolic Syndrome - Zhang, Li; Zhang, Zizhe; Wang, Bangxuan; Yuan, Yongting; Sun, Lili; Gao, Huaiquan; Fu, Lianguo (Frontiers in Endocrinology, 2021)
Background: The children’s lipid accumulation product (CLAP) is associated with MS in Chinese children and adolescents. The aim of this study was to develop a more effective indicator, the relative children's lipid accumulation product (RCLAP) was evaluated for correlation with MS and the density of lipid accumulation. Methods: A stratified cluster sampling method was used to recruit 683 students aged 8-15 years in this study. The presence of MS was defined according to the NCEP-ATP III criteria. The participants’ guardians signed informed consent before the medical examination. This study was approved by the Medical Ethics Committee of the Bengbu Medical College ([2015] 100 No.003) and was conducted in accordance with the Declaration of Helsinki. Results: The overall prevalence of MS was 4.8% (male 6.6%, female 2.8%). After adjusting for sedentary activity time, relative children's lipid accumulation product per height (RCLAP-H) and relative children's lipid accumulation product per sitting height (RCLAP-SH) significantly increased the risk of MS in girls (OR (95% CI): 96.13 (11.11-831.97) and 96.13 (11.11-831.97), respectively). After adjusting for ages and moderate-to-vigorous physical activity time, RCLAP-H, and RCLAP-SH significantly increased the risk of MS in boys (OR (95% CI): 171.75 (33.60-878.00) and 133.18 (27.65-641.39), respectively). The AUCs of RCLAP-H and RCLAP-SH for predicting MS were 0.950, 0.948 in girls, and 0.952, 0.952 in boys, which were higher than BMI, WHtR, Tg/HDL-C, CLAP and CLAP combining height, sitting height. Conclusions: The RCLAP-H and RCLAP-SH were more effective indicators for predicting MS than BMI, WHtR, Tg/HDL-C and CLAP in children and adolescents.